Aortic valve fibroelastoma: a rare cause of stroke. (22nd November 2016) - Kumar, Vivek; Soni, Parita; Hashmi, Arsalan; Moskovits, Manfred
Abstract : The prevalence of primary cardiac tumours varies from 0.02% to 0.45%. Cardiac papillary fibroelastoma (CPF) is a rare tumour diagnosed incidentally on imaging. The clinical manifestations result from thromboembolisation and include transient ischaemic attack, stroke and sudden cardiac death. We present a patient aged 57 years with CPF arising from the aortic valve. The patient presented with right hemiparesis due to acute stroke. He received tissue plasminogen activator with complete resolution of neurological symptoms. Echocardiography revealed a broad-based, gelatinous, non-mobile mass on the left aortic cusp. The tumour was excised sparing the aortic valve. The patient recovered rapidly without any complications. The histopathological examination confirmed the diagnosis of CPF. A review of the literature suggests that CPF is a rare but treatable cause of stroke. The course is not clear and there are no tumours or patient-related characteristics which could predict the risk of thromboembolisation. Surgical treatment is definite and is relatively safe.